2019
DOI: 10.1029/2019gl083026
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Tropical Ascent and High Cloud Fraction Changes With Warming Revealed by Perturbation Physics Experiments in CAM5

Abstract: Tropical ascent area (Aa) and high cloud fraction (HCF) are projected to decrease with surface warming in most Coupled Model Intercomparison Project Phase 5 (CMIP5) models. Perturbing deep convective parameters in the Community Atmosphere Model (CAM5) results in a similar spread and correlation between HCF and Aa responses to interannual warming compared to the CMIP5 ensemble, with a narrower Aa corresponding to greater HCF reduction. Perturbing cloud physics parameters produces a comparatively smaller range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
2
11
4
Order By: Relevance
“…But what we actually see is a decrease in up , because the mean heating rate in the ascending region is also intensifying, and at a faster rate than the cooling over the descending region (i.e., −Q up ∕Q dn increases). This provides support for the suggestion of Schiro et al (2019) that changes to convection in the ascending region are closely linked to changes in ascent area with warming.…”
Section: Mean Circulationsupporting
confidence: 81%
See 1 more Smart Citation
“…But what we actually see is a decrease in up , because the mean heating rate in the ascending region is also intensifying, and at a faster rate than the cooling over the descending region (i.e., −Q up ∕Q dn increases). This provides support for the suggestion of Schiro et al (2019) that changes to convection in the ascending region are closely linked to changes in ascent area with warming.…”
Section: Mean Circulationsupporting
confidence: 81%
“…Simulations of the future climate are sensitive to convective parameterizations (e.g., Maher et al, 2018). Models participating in the Coupled Model Intercomparison Project Phase 5 vary widely in their projections of the strength of the mean tropical circulation (Byrne et al, 2018), mostly due to differences in convective parameterizations between the models (Schiro et al, 2019). The resulting uncertainties can be avoided by using global convection-resolving models (CRMs; e.g., Stevens et al, 2019), but for now the high computational cost of such models limits their use in global climate change simulations.…”
Section: Modelmentioning
confidence: 99%
“…Even with the same SST patterns in all the AMIP runs, the differences in the model physics, especially the moist convective schemes (Schiro et al, ), can still create large intermodel spread in the tightening trend, as shown in Figure and Table S2. Su et al () found that model differences in the cloud radiative effects at the top of atmosphere over deep convective regions are highly correlated with the diverse responses in the ascent intensity and area changes, indicating a strong coupling between circulation and clouds.…”
Section: Resultsmentioning
confidence: 99%
“…All the simulations are found to reach an equilibrium state within 30 years (the top-of-atmosphere [TOA] net radiation flux close to 0 and surface temperature stabilized), and our analyses are based on the averages of the last 10 years. Note that for those parameter-perturbed experiments, the new equilibrium states are slightly different with the present-day climate in terms of the TOA atmospheric radiative fluxes and/or global mean surface temperature, but the responses in the atmospheric states are still valuable to reflect the importance of certain model parameters, as done in many previous modeling works (Qian et al, 2015;Schiro et al, 2019;Tan et al, 2016). We choose not to tune the TOA radiative fluxes back to the observational values, because such a tuning can exert marked influence on the model's climate sensitivity and overshadow the effects of parameter perturbation in this study.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Over the tropics, radiative warming arising from high-altitude ice cloud can be as large as +80 W m −2 at the top of atmosphere (Stephens et al, 2002). Hence, radiative properties of ice clouds are crucial in regulating the Earth's radiation and energy balance and altering the climate feedbacks and climate sensitivity (e.g., Sanderson et al, 2007;Schiro et al, 2019;Su et al, 2017). Ice particle size is a critical physical property which is closely related with the cross section for longwave absorption and efficiency of shortwave scattering (Fu & Liou, 1993;Liu et al, 2014).…”
Section: Motivation and Backgroundmentioning
confidence: 99%